A prayer journal - O'Connor, Flannery (Farrar, Straus, and Giroux, 2013)
Written between 1946 and 1947, while O'Connor was a student far from home at the University of Iowa, this spiritual journal was only recently discovered. It provides a rare portal into the interior life of a great writer, and is a record of a young woman's cry from the heart for love, grace, and art.